2013
DOI: 10.1136/bmj.f3501
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic ketoacidosis: not always due to type 1 diabetes

Abstract: This article discusses how to diagnose and manage patients with ketosis prone type 2 diabetes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 20 publications
2
35
0
Order By: Relevance
“…12 Mishra et al has reviewed the pathophysiology of DKA prone T2DM in his recent article and shown that DKA is not just the feature restricted to T1DM but can also be a complication of T2DM usually with a precipitating factor. 13,14 Wang et al in their study also supported similar findings of DKA in T2DM patients. 3 Mean age of patients in present study was 56.10±10.40 years.…”
Section: 10supporting
confidence: 59%
“…12 Mishra et al has reviewed the pathophysiology of DKA prone T2DM in his recent article and shown that DKA is not just the feature restricted to T1DM but can also be a complication of T2DM usually with a precipitating factor. 13,14 Wang et al in their study also supported similar findings of DKA in T2DM patients. 3 Mean age of patients in present study was 56.10±10.40 years.…”
Section: 10supporting
confidence: 59%
“…1 Subsequent fluid administration depends on the patient's haemodynamic status and which guideline is being followed, with the American Diabetes Association recommending 0.45% saline if the sodium level is normal or high 7 and the Joint British • There may be no obvious precipitant, 8 for example, in ketosis-prone diabetes (an atypical form of type 2 diabetes), in which DKA is the presenting condition but insulin can later be discontinued.…”
Section: Intravenous Fluidsmentioning
confidence: 99%
“…30 The National Institute for Health and Care Excellence (NICE) should review the current HbA1C target of 7.0% in light of increasing emergency admissions with hypoglycaemia. In addition, GPs should follow NICE recommendations for patients who have experienced hypoglycaemia and ensure they have an individualised HbA1C target.…”
mentioning
confidence: 99%